The Impact of Inflation, Foreign Trade and Exchange Rates on Economic Growth in 5 ASEAN Countries - Atika, Dina; Fahriansah; Astina, Chahayu (LP2M IAIN Palopo, 2025)
This study aims to examine and analyze the partial and simultaneous influence of inflation , foreign trade , and exchange rates on economic growth in ASEAN countries . This study uses quantitative methods and descriptive data analysis. The sample in this study is five ASEAN countries . which was first formed . The results of this study indicate that inflation partially has a positive and significant effect on economic growth in ASEAN countries . With a probability value of 0.0247 <0.05, while the calculated T and T table values are 2.1161 > 2.01290 . The import probability value is 0.0478 <0.05, while the calculated T and T table values are 2.0112 > 2.01290. The import probability value is 0.3595 > 0.05, while the calculated T and T table values are 0.9741 <2.01290. The exchange rate probability value is 0.2086 > 0.05, while the calculated T and T table values are 1.0207 <2.01290. And the Prob F-Statistic value is 0.000015. Since the F-Statistic value is 0.000015 < 0.05, Ha is rejected and Ho is accepted. Therefore, it can be concluded that inflation, exports, imports, and exchange rates simultaneously have a positive and significant effect on economic growth in ASEAN countries.